2005
DOI: 10.1210/jc.2005-0231
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Inflammation and Estimates of Insulin Resistance during the Menstrual Cycle in Lean and Overweight Women

Abstract: We demonstrate that serum concentrations of hs-CRP and SHBG significantly change during the menstrual cycle. We reveal a close link between sex steroids, subclinical inflammation, insulin resistance, and body fat distribution in regularly menstruating women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 37 publications
11
71
3
2
Order By: Relevance
“…In the present study, we could not confirm cycle-dependent CRP variations in a clearly larger patient group and we did not find any correlation with E2. The differences between the results of Blum et al (30) and the present data can most likely be explained by the nearly four times larger sample size and the slightly shorter (and thus more sensitive) intervals between samplings (2 days maximum) in our study. In another study on CRP levels in the menstrual cycle with 18 patients (29), a CRP increase of 44% at midcycle and 31% in the luteal phase in comparison to follicular phase levels were found.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, we could not confirm cycle-dependent CRP variations in a clearly larger patient group and we did not find any correlation with E2. The differences between the results of Blum et al (30) and the present data can most likely be explained by the nearly four times larger sample size and the slightly shorter (and thus more sensitive) intervals between samplings (2 days maximum) in our study. In another study on CRP levels in the menstrual cycle with 18 patients (29), a CRP increase of 44% at midcycle and 31% in the luteal phase in comparison to follicular phase levels were found.…”
Section: Discussioncontrasting
confidence: 99%
“…Concerning the inflammatory mediator CRP, only a few trials with low number of subjects have been studying its concentration pattern during the normal spontaneous cycle. Blum et al (30) recently investigated eight young, normal-weight women with normal ovarian function and found that CRP concentrations changed significantly during the menstrual cycle. Concentrations were highest in the early follicular phase and inversely correlated to E2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…26 Plasma was separated by centrifugation for 20 min at 2500 r.p.m. and 41C for the measurement of all inflammatory markers, cell adhesion molecules glucose and insulin, as well as TG, total cholesterol (total-C), low-density lipoproteins (LDL-C) and high-density lipoproteins (HDL-C) assessed by standard colorimetric reflectance spectrophotometry at the Fairview Diagnostics Laboratories, FairviewUniversity Medical Center (Minneapolis, MN, USA), a Center for Disease Control and Prevention certified laboratory.…”
Section: Blood Chemistry Measuresmentioning
confidence: 99%
“…In women of reproductive age, detection of basal CRP levels in diff erent phases of the menstrual cycle has been evaluated previously [14][15][16][17][18][19][20][21][22][23]. Nevertheless, the data about menstrual cycle variability of CRP is confl icting.…”
Section: Introductionmentioning
confidence: 99%